Analysis of damage and interlaminar stresses in laminate plates with interacting holes. (1st January 2020) - Solis, A.; Barbero, E.; Sánchez-Sáez, S.
Highlights: Interaction between two holes in laminates subjected to compressive loads was analysed. Fibre damage initiation and propagation was very different from the matrix damage. Failure initiation was due to fibre microbuckling in the plies at 0°. A second hole does not necessarily imply an increase in interlaminar stresses. Abstract: In a laminate plate with an open hole, the damage initiation and progression and the interlaminar stresses that appear close to hole edge are modified when a second hole is made close to the first. The purpose of this study is to analyse the interaction between two holes when the plate is subjected to compressive loads. The Serial/Parallel Mixing Theory is used as the constitutive law of the composite, and a Continuum Damage Model is applied to predict failure initiation and propagation due to fibre microbuckling and matrix cracking. The model is validated using data from the literature. The developed model is able to predict the differences in the initiation and propagation of damage due to fibre microbuckling and matrix cracking in the area around the two holes. The variation of the distance between holes significantly modifies the damage due to both mechanisms. Also, the interlaminar stresses along the laminate thickness are changed. The results of this study can be applied to predict the critical distance between holes to avoid damage initiation by matrix cracking and microbuckling.